Postgraduate students conception of language assessment - Nimehchisalem, Vahid; Mat Hussin, Nur Izyan Syamimi (BioMed Central, 2018)
Background: Assessment is an essential part of any learning process; however, it is often disliked by most students. A wealth of research is available on issues on assessment, such as washback effect and test anxiety, and yet we know little about what students conceive of assessment. The objective of this case study was to explore a group of postgraduate students’ conception of language assessment. Methods: The participants of this qualitative study were an intact group of postgraduate students (n = 21) who completed two tasks. The first task was creating a metaphor by completing the sentence “A world without assessment is…” and then explaining the metaphor. To fulfil the second task, the participants wrote a short story each related to language assessment. The collected data were analyzed thematically. Results: Interesting metaphors emerged. The metaphors covered four purposes of assessment, including “to guide,” “to motivate,” “to empower,” and “to control” with frequencies of 9, 6, 3, and 3, respectively. For example, assessment was viewed as a map (guide), reward (motivation), driver’s license (empowerment), and iron fist (control). In the short stories, the most frequent themes that recurred were “cheating,” “test anxiety,” and “motivation tool” with frequencies of four each. The themes which were the least frequent were “fair assessment,” “promoting learner collaboration,” “teaching to the test,” and “biased assessment” each occurring only once. Conclusion: The results show that collectively students are well aware of the purposes of assessment but their experiences with assessment illustrate cases of language assessment which indicate room for improvement in the way assessment is understood and administered.